DICER1 and FOXL2 mutations in ovarian sex cord–stromal tumours: a GINECO Group study. Issue 2 (21st July 2015) - Goulvent, Thibault; Ray‐Coquard, Isabelle; Borel, Stéphane; Haddad, Véronique; Devouassoux‐Shisheboran, Mojgan; Vacher‐Lavenu, Marie‐Cecile; Pujade‐Laurraine, Eric; Savina, Ariel; Maillet, Denis; Gillet, Germain; Treilleux, Isabelle; Rimokh, Ruth
Abstract : Aims: FOXL2 mutation has been consistently identified in adult granulosa cell tumours (A‐GCTs). DICER1 mutations have been described predominantly in Sertoli–Leydig cell tumours (SLCTs). The prognostic implication of these mutations remains uncertain, as moderately sized studies have yielded variable outcomes. Our aim was to determine the implications of DICER1 and FOXL2 mutations in 156 ovarian sex cord–stromal tumours (SCSTs). Methods and results: FOXL2 mutations were found in 94% of pathologically confirmed A‐GCTs (95/101), in one of eight juvenile granulosa cell tumours (J‐GCTs), and in two of 19 SLCTs. DICER1 mutations in the RNase IIIb domain were found in six of 19 SLCTs, two of eight J‐GCTs, and one of 12 undifferentiated SCSTs (Und‐SCSTs). Comparison of DICER1 ‐mutated SLCTs with DICER1 ‐non‐mutated SLCTs showed that patient age at diagnosis was lower and oestrogen receptor expression was more frequent in DICER1 ‐mutated tumours. With a median follow‐up of 22 months, two of five DICER1 ‐mutated SLCTs relapsed, in contrast to none of eight DICER1 ‐non‐mutated tumours. Conclusions: Our results suggest that, in contrast to FOXL2 mutations in A‐GCT, DICER1 mutations in SLCT might be more useful for prognosis than for diagnosis. However, study of a larger cohort of patients is necessary to establish this. Identification of genetic alterations in SCST offers promising therapeutic options.